1993
DOI: 10.1128/jcm.31.6.1493-1503.1993
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of serotype-specific, immunodominant epitopes in the NS-4 region of hepatitis C virus (HCV): use of type-specific peptides to serologically differentiate infections with HCV types 1, 2, and 3

Abstract: The effect of sequence variability between different types of hepatitis C virus (HCV) on the antigenicity of the NS-4 protein was investigated by epitope mapping and by enzyme-linked immunosorbent assay with branched oligopeptides. Epitope mapping of the region between amino acid residues 1679 and 1768 in the HCV polyprotein revealed two major antigenic regions (1961 to 1708 and 1710 to 1728) that were recognized by antibody elicited upon natural infection of HCV. The antigenic regions were highly variable bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
4

Year Published

1995
1995
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(101 citation statements)
references
References 59 publications
5
91
1
4
Order By: Relevance
“…17 HCV genotyping was done using the reverse hybridization assay (line probe assay, LiPA; Innogenetics, Ghent, Belgium) 18 and serotyping by immunoassays based on serological differences in antibody to the NS4 region of the genome. 19 As a part of the initial study, all patients underwent liver biopsy before treatment and again after 1 year of treatment. Subsequently, follow-up liver biopsies were done on all 10 patients between 5 and 11 years after starting therapy.…”
Section: Patientsmentioning
confidence: 99%
“…17 HCV genotyping was done using the reverse hybridization assay (line probe assay, LiPA; Innogenetics, Ghent, Belgium) 18 and serotyping by immunoassays based on serological differences in antibody to the NS4 region of the genome. 19 As a part of the initial study, all patients underwent liver biopsy before treatment and again after 1 year of treatment. Subsequently, follow-up liver biopsies were done on all 10 patients between 5 and 11 years after starting therapy.…”
Section: Patientsmentioning
confidence: 99%
“…All patients were characterized with respect to the infecting HCV subtype either using the INNOLIPA test (Innogenetics, Zwijndrecht, Belgium) or, because of the absence of HCV-RNA in sera from subjects with self-limited infection, using serotype-specific antibodies to the NS4 region (Murex, Groß Burgwedel, Germany) [20]. Thus, at least HCV genotypes, but not subtypes, could be determined in the patients with previous HCV infection.…”
Section: Determination Of Infecting Hcv Genotypesmentioning
confidence: 99%
“…Although the immune response to HCV in chimpanzees may differ from that of humans, it is likely that in haemophiliacs multiple exposure from long-term use of non-heated concentrates may have led to several episodes of reinfection, and possibly an increased likelihood of acquiring highly pathogenic variants when compared with singly exposed individuals. Multiple episodes of acute hepatitis, associated with reinfection with homologous genotypes have been documented in multi-transfused thalassaemic children [36] and multiple infections have been detected in a variety of polytransfused patients [ 11, [37][38][39].…”
Section: Immunity To Hcvmentioning
confidence: 99%
“…The patient samples described above were also tested for type-specific antibody by an indirect ELlSA [37]. We have found that many patients showing changes in genotype often showed parallel but delayed changes in type-specific antibodies to NS-4 peptides [32].…”
Section: Hcv Serologymentioning
confidence: 99%